Characterization and Design of Zeolite Catalysts Solid Acidity, Shape Selectivity and Loading Properties - Niwa, Miki.; Katada, Naonobu; Okumura, Kazu.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Zeolites are microporous, aluminosilicate minerals commonly used as commercial adsorbents. Zeolite-based catalysts are used by industrial chemical companies in the interconversion of hydrocarbons and the alkylation of aromatic compounds. The current book deals with the characterization of specific properties of Zeolites and calculations for the design of catalysts. Measurements and utilization of solid acidity, shape selectivity, and loading properties, that are three prominent properties of a Zeolite catalyst, are treated in detail. These features concern chemical vapor deposition of silica, shape selectivity, loading properties, solid activity, Brønsted or Lewis character, ammonia temperature programmed desorption, control of the pore-opening size by chemical vapor deposition of silica and XAFS analysis of metals being highly dispersed inside and outside a framework.
to Zeolite Science and Catalysis -- Solid Acidity of Zeolites -- IRMS-TPD Measurements of Acid Sites -- DFT Calculation of the Solid Acidity -- Catalytic Activity and Adsorption Property -- CVD of Silica for the Shape Selective Reaction -- Application of the CVD of Silica to the Shape Selective Reaction -- Zeolite Loading Property for Active Sites and XAFS Measurements -- Catalytic Reaction on the Palladium-Loaded Zeolites.
Keywords: Chemistry; Physical chemistry; Condensed matter; Structural materials; Materials science; Chemistry; Physical Chemistry; Characterization and Evaluation of Materials; Condensed Matter Physics; Structural Materials; Electronic books